Experimental Study on Nanofluid Flow in a Porous Cylinder: Viscosity, - Miguel, A. F. (2015)
Knowledge of fluid rheology and flow characteristics is important when studying nanofluid flow in porous media. In this study, an experimental investigation is presented to determine the nanofluid viscosity, the permeability and the inertial(non-Darcy) parameter of a porous cylinder made of several capillary tubes. The applicability of the Darcy-Forchheimer equation for power-law fluids to estimate pressure drop through the porous material is discussed. The occurrence of particle losses from the base fluid (deposition) is also verified. Experiments are completed in two steps. In the first step, physical properties of nanofluids consisting of deionized water and different volume concentrations of Al2O3 nanoparticles is measured. In the second step, Al2O3-deionized water nanofluids are pumped through a porous cylinder (porosity 0.249) to evaluate hydraulic and intrinsic permeabilities, and the inertial parameter. The effect of Al2O3 volume fraction on these flow properties is studied, and the void morphology changes within the porous cylinder via deposition of nanoparticles are analyzed.